The Anger of the Main Character in the Perempuan Bersampur Merah Novel by Intan Adaru: A Study of Literary Psychology - Sariban Sariban; Hendrik Furqon; M Ibad Sang Babil; Rahayu Tanti Retno; Choirun Nisa’; Nafa Wahyuningtyas Eka Putri (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2020)
This study aims to describe (1) the form of anger of the main character in the novel